PRIORITIES AND DIRECTIONS OF THE STATE INFORMATION POLICY IN THE FIELD OF YOUTH MEDIA CULTURE DEVELOPMENT (Scientific journal of the Fergana State University, 2026)
This article analyzes the theoretical and methodological foundations of the development of youth media culture in New Uzbekistan, the scientific and philosophical analysis of the development of youth media culture in New Uzbekistan, and the priority tasks of the development of youth media culture in New Uzbekistan. The article studies the priority tasks and directions of state information policy in the development of youth media culture.